Age estimation by using aspartic acid racemization from purified elastin of aorta - Komutrattananont P,; Pasuk Mahakkanukrauh, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Age estimation is the one of biological profiles which plays an important role in identification in forensic field. The application of biochemical approach known as aspartic acid racemization in human provides more accuracy and less error of estimated age in age determination. During aging, amino acids within protein transform between D-and L-form (racemization), which results in increasing concentration of D-amino acids. This change of amino acids is related to aging. Aspartic acid has been generally applied in racemization because it has fastest rate of racemization. Racemization of aspartic acid not only takes place in teeth and many kinds of bone, but also can occur in the flexible structure which contain mostly elastin. For example, skin yellow ligament, lung parenchyma, and aorta. Elastin is essential protein which is comprised most composition of several structures and it is major content in the elastic fibers. Additionally, elastin is the longest lasting protein in the body with slow metabolic turnover rate. Recently, there is a purification technique to obtain only single protein in human aorta. There was a good correlation between degree of racemization (D/L ratio) and age. Therefore, aspartic acid racemization by purifies elastin from aorta is a one of indicator for age estimation. This review provides an overview of aspartic acid racemization, elastin protein, purification method bases on racemization and the application of D/L ratio by purified of elastin in artery for age estimation.